Religio-politics of Islamic Group in the Contestation of 2019 Indonesian Presidential Election - Winarni, Leni; Agussalim, Dafri; Bagir, Zainal Abidin (Political Science Program, Universitas Negeri Semarang, 2020)
In spite of the fact that Islamic identity politics is not a new theme in Indonesia, this phenomenon is increasing in the public sphere after the 1998 reform. This is marked by the frequent use of religious issues in the political contestations such as the 2017 DKI Jakarta Gubernatorial election and the 2019 Presidential election. In the DKI election, certain Islamic groups demanded Basuki Tjahaya Purnama, who from the double minority group, as a subject due to blasphemy issue. However, in 2019 Presidential election which Joko Widodo and Prabowo Subianto rematched for the second candidacy, religious issues were also raising. Political contestation continued despite the fact that the two presidential candidates are Muslim. This interesting fact certainly raises the question of the phenomenon of national politics which leads not only to the strengthening of Islamic identity politics but also the identity politicsbetween Islamic groups in Indonesia. Based on field studies, literatures and interviews, this study will discuss the construction process of the identity politics of Islamic groups against social and political reality nowadays, moreover in the 2019 Presidential Election. In contrast to the other researches that still focuses on why identity politics arises, this research will examine the construction process, moreover in the 2019 Presidential election.